2016
DOI: 10.1097/md.0000000000002670
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Compression Fracture Related to Pancreatic Cancer With Osteoblastic Metastasis

Abstract: Compression fracture of the vertebral body is common in the older patients. The possible etiology like osteoporosis or cancer metastasis should be included as a possibility in the differential diagnosis for severe back pain, to prevent delays in diagnosis and treatment. More severe fractures can cause significant pain, leading to inability to perform activities of daily living, and life-threatening in the older patient.We report a rare case of a 61-year-old man suffering from severe lower back pain and intermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 22 publications
1
15
1
Order By: Relevance
“…Chih et al reported a patient with L2 vertebra involvement treated with percutaneous vertebroplasty with an improvement of performance status and pain control. 40 Survival of our patient was lower than the median overall survival of a metastatic PDAC patient treated with firstline gemcitabine and nab-paclitaxel. In previous reports, we described a relationship between bone metastases and poorer prognosis in patients affected by gastric cancer and hepatocellular carcinoma.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Chih et al reported a patient with L2 vertebra involvement treated with percutaneous vertebroplasty with an improvement of performance status and pain control. 40 Survival of our patient was lower than the median overall survival of a metastatic PDAC patient treated with firstline gemcitabine and nab-paclitaxel. In previous reports, we described a relationship between bone metastases and poorer prognosis in patients affected by gastric cancer and hepatocellular carcinoma.…”
Section: Discussioncontrasting
confidence: 58%
“…Few reports described the role of surgery in the management of bone involvement in PDAC. Chih et al reported a patient with L2 vertebra involvement treated with percutaneous vertebroplasty with an improvement of performance status and pain control …”
Section: Discussionmentioning
confidence: 86%
“…One study identified seven patients from a database of 323 PDAC patients (2.2%) with skeletal metastases. [ 4 ] In this series, 57.1% of patients were symptomatic, with the most common metastatic locations being the vertebrae, hips, and ribs. Two additional studies reported small osteoblastic L2[ 9 ] and L3[ 7 ] vertebral body metastatic lesions due to pancreatic adenocarcinoma in the body of the pancreas.…”
Section: Discussionmentioning
confidence: 82%
“…In KEGG, as shown in Table 3, some of these pathways were specific to cancer development, such as pancreatic cancer and prostate cancer. Accumulated evidence has proved that bone metastasis and bone loss are significant symptoms in these cancers, especially in the later stages (Chih et al, 2016;Poulsen et al, 2019). According to previous reports, p53 signaling pathway is involved in regulating osteoblast production and apoptosis and affecting BMD (Zhen et al, 2014;Liu W. et al, 2015).…”
Section: Pathway-level Analysismentioning
confidence: 98%